Investigation on Multiferroic Properties and Conduction Mechanism in Cobalt Doped Bi0.9Nd0.1FeO3 Solid Solutions. Issue 2 (3rd April 2021) - Kumar, Anil; Sharm, Preeti; Pal, Jaswinder; Singh, Anupinder; Kundu, Rajender Singh; Punia, Rajesh
Abstract : Bi0.9 Nd0. 1 Fe1– x Co x O3 ( x = 0.025, 0.050, 0.075 and 0.1) solid solutions have been synthesized by doping of Co 3+ at the Fe 3+ site using solid-state reaction method. The prepared solid solutions have been investigated for their structural, magnetic, ferroelectric and magneto-dielectric properties and conduction mechanism. The XRD study reveals that all the solid solutions possess a rhombohedral symmetry. The vibrating sample magnetometer study reveals that all the samples possess magnetic orders and the remnant magnetization has been found to be increased from 0.2388 emu/g for x = 0.025 to 0.7112 emu/g for x = 0.1. The non-Debye type dielectric relaxation has been investigated for all the samples. The frequency dependent ac conductivity data follows Jonscher's Power law. Variation of exponent n versus temperature follows the overlapping large polaron tunneling conduction model. The maximum value of remanent polarization (∼0.152 μC/cm 2 ) was found for x = 0.1. All the samples exhibit positive magneto-dielectric response in the low-frequency region with the highest magneto-capacitance value of 13.54% at 500 Hz for sample x = 0.1. GRAPHICAL ABSTRACT: UF0001